Analisis Kesenjangan antara Teori dan Praktik mengenai Membiasakan Perilaku Sesuai Nilai Sila Kemanusiaan yang Adil dan Beradab Dalam Kehidupan Masyarakat (Analisis Isi Buku Pendidikan Pancasila dan Kewarganegaraan Terbitan Kementrian Pendidikan dan Kebudayaan Republik Indonesia Kelas VIII SMP/MTs Kurikulum 2013 dan Berita di Media Internet atau Online) - Muliana Kasmorani, Putri, Dra. Hj. Sri Arfiah, S.H., M.Pd (2015)
This research is to describe the assymmetry of the practical theory about the value of moral humanity which is fair and cultured in social life based on the Pendidikan Pancasila book and citizenship which is published by the educational ministry and culture Republic of Indonesia grade VIII 2013 curriculum with the news in internet or online. This research is qualitative research. The source for this research is Pendidikan Pancasila and Citizenship Republic of Indonesia grade VIII 2013 curriculum and internet or online. The technique for collect the data use documentation method and literature. The validity of the data will be test using triangulation of the data source and triangulation of the technique for collecting the data. This research can be concluded that, there is the asymmetry of the value of moral humanity wich is fair and cultured in social life. Between the theory which is in the pendidikan pancasila and citizenshp book published by the ministry of education and cultured Republic of Indonesia grade VIII 2013 curriculum with the pratical in social life which is get from the internet or online. The asymmetry can be seen by the the diverge of phenomenon from the present theory. The behaviour of the people do not reflect from the book.